2013
DOI: 10.1097/gme.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of walking on the preservation of bone mineral density in perimenopausal and postmenopausal women

Abstract: Walking as a singular exercise therapy has no significant effects on BMD at the lumbar spine, at the radius, or for the whole body in perimenopausal and postmenopausal women, although significant and positive effects on femoral neck BMD in this population are evident with interventions more than 6 months in duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 32 publications
3
63
2
5
Order By: Relevance
“…Another study (9) confirmed that walking as a singular exercise therapy has no significant effects on BMD at the lumbar spine, at the radius, or for the whole body in perimenopausal and postmenopausal women, although significant and positive effects on femoral neck BMD are evident with interventions with more than 6 months in duration. It seems that only the impact of a brisk walking is not enough to stimulate spine BMD in ambulatory postmenopausal women.…”
Section: Impact and Aerobic Exercisesmentioning
confidence: 71%
“…Another study (9) confirmed that walking as a singular exercise therapy has no significant effects on BMD at the lumbar spine, at the radius, or for the whole body in perimenopausal and postmenopausal women, although significant and positive effects on femoral neck BMD are evident with interventions with more than 6 months in duration. It seems that only the impact of a brisk walking is not enough to stimulate spine BMD in ambulatory postmenopausal women.…”
Section: Impact and Aerobic Exercisesmentioning
confidence: 71%
“…Further, aerobic exercise and calorie restriction improves insulin sensitivity and reduces the risk of diabetes in postmenopausal women [87]. Decrease in bone mineral density is associated with post menopause, and, walking for more than 6 months improves femoral neck bone mineral density in menopause women as analysed in 10 different trials [88]. Further, skeletal muscle regeneration efficiency declines with age and is related to the decline in sex hormones.…”
Section: Exercise Beyond Menopausementioning
confidence: 99%
“…Evidence from systematic review and meta-analysis clearly show than physical exercise induce an improvement bone mass content in older women (7)(8)(9). Controlled trials in post-menopausal women have been considered physical exercise along with medication and diet one of the three cornerstones of osteoporosis (10,11).…”
Section: Introductionmentioning
confidence: 99%